Maize millers in Kenya adopt a quality control approach to testing maize for aflatoxins ensuring safer maize is available for 10 million Kenyan consumers - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
The Aflatoxin Proficiency and Testing and Control in Africa (APTECA) program has improved the way maize millers in the Kenya Cereals Association measure and manage aflatoxin risk. This has meant that maize products introduced into Kenyan markets do not exceed maximum aflatoxin levels, improving food safety for about 10 million consumers. APTECA was hosted from 2014-2016 by the Biosciences eastern and central Africa - International Livestock Research Institute Hub and has collaborated with IFPRI on research that informed implementation.